Dielectric engineering enable to lateral anti-ambipolar MoTe2 heterojunction. (23rd April 2022) - Geng, Guangyu; Wu, Enxiu; Xu, Linyan; Hu, Xiaodong; Miao, Xiaopu; Zou, Jing; Wu, Sen; Liu, Jing; Liu, Yang; He, Zhongdu
Abstract: Atomically two-dimensional (2D) materials have generated widespread interest for novel electronics and optoelectronics. Specially, owing to atomically thin 2D structure, the electronic bandgap of 2D semiconductors can be engineered by manipulating the surrounding dielectric environment. In this work, we develop an effective and controllable approach to manipulate dielectric properties of h-BN through gallium ions (Ga + ) implantation for the first time. And the maximum surface potential difference between the intrinsic h-BN (h-BN) and the Ga + implanted h-BN (Ga + -h-BN) is up to 1.3 V, which is characterized by Kelvin probe force microscopy. More importantly, the MoTe2 transistor stacked on Ga + -h-BN exhibits p-type dominated transfer characteristic, while the MoTe2 transistor stacked on the intrinsic h-BN behaves as n-type, which enable to construct MoTe2 heterojunction through dielectric engineering of h-BN. The dielectric engineering also provides good spatial selectivity and allows to build MoTe2 heterojunction based on a single MoTe2 flake. The developed MoTe2 heterojunction shows stable anti-ambipolar behaviour. Furthermore, we preliminarily implemented a ternary inverter based on anti-ambipolar MoTe2 heterojunction. Ga + implantation assisted dielectric engineering provides an effective and generic approach to modulate electric bandgap for a wide variety of 2D materials. And the implementation of ternary inverter based on anti-ambipolar transistor could lead to new energy-efficient logical circuit and system designs in semiconductors.